THE EFFECT OF DIFFERENT WATER LEVELS ON THE GROWTH AND SURVIVAL RATE OF CACHAMA (Colossoma macropomum) LARVAE - Romansah, Danang Prasetyo; Aryani, Netti; Nuraini, Nuraini (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
The study was conducted from March to May 2022 at the Fish Hatchery and Breeding Laboratory of the Fishery and Marine Science Faculty, Universitas Riau. This research aimed to determine the effect of the best water level on the growth and survival rate of cachama larvae (Colossoma macropomum). This study used a factorial completely randomized design (CRD) with four treatments and three replications. The treatments used were P1 = water level 5cm, P2 = water level 10cm, P3 = water level 15cm, and P4 = water level 20cm. Larvae were reared for 40 days with a stocking density of 2 fish/L. Different water levels showed a significant effect on the growth of absolute weight, absolute length, and specific growth rate of cachama larvae and no effect on the survival of cachama larvae (p<0.05). The best treatment was at a water level of 5 cm, with absolute growth of 1.73 g, absolute length of 4.59 cm, specific growth rate (SGR) of 17.16%/day, and survival rate of 91.11%. Water quality parameters during the study were temperature ranging from 26.7-28.4℃, pH 6.0-6.9, and dissolved oxygen ranging from 5.2-5.9 mg/L.